Genome-wide identification and expression analysis of the cellulose synthase gene family in potato (Solanum tuberosum L.) - Gong, Huiling; Ma, Junxian; Dusengemungu, Leonce; Feng, Zaiping (Frontiers in Plant Science, 2024)
Potato (Solanum tuberosum) is the fourth largest staple food crop globally. However, potato cultivation is frequently challenged by various diseases during planting, significantly impacting both crop quality and yield. Pathogenic microorganisms must first breach the plant's cell wall to successfully infect potato plants. Cellulose, a polysaccharide carbohydrate, constitutes a significant component of plant cell walls. Within these walls, cellulose synthase (CesA) plays a pivotal role in cellulose synthesis. Despite its importance, studies on StCesAs (the CesA genes in potato) have been limited. In this study, eight CesA genes were identified and designated as StCesA1-8, building upon the previous nomenclature (StCesA1-4). Based on their phylogenetic relationship with Arabidopsis thaliana, these genes were categorized into four clusters (CesA I to CesA IV). The genomic distribution of StCesAs spans seven chromosomes. Gene structure analysis revealed that StCesAs consist of 12 to 14 exons. Notably, the putative promoter regions harbor numerous biologically functional cis-acting regulatory elements, suggesting diverse roles for StCesAs in potato growth and development. RNA-seq data further demonstrated distinct expression patterns of StCesAs across different tissues. Additionally, quantitative real-time PCR (QRT-PCR) results indicated significant up-regulation of StCesA5 expression under biotic stresses, implicating its potential involvement in potato disease resistance.